Biochar and Manure Applications Differentially Altered the Class 1 Integrons, Antimicrobial Resistance, and Gene Cassettes Diversity in Paddy Soils - Ali, Niyaz; Lin, Yinfu; Jiang, Ligeng; Ali, Izhar; Ahmed, Ishtiaq; Akhtar, Kashif; He, Bing; Wen, Ronghui (Frontiers in Microbiology, 2022)
Integrons are genetic components that are critically involved in bacterial evolution and antimicrobial resistance by assisting in the propagation and expression of gene cassettes. In recent decades, biochar has been introduced as a fertilizer to enhance physiochemical properties and crop yield of soil, while manure has been used as a fertilizer for centuries. The current study aimed to investigate the impact of biochar, manure, and a combination of biochar and manure on integrons, their gene cassettes, and relative antimicrobial resistance in paddy soil. Field experiments revealed class 1 (CL1) integrons were prevalent in all samples, with higher concentration and abundance in manure-treated plots than in biochar-treated ones. The gene cassette arrays in the paddy featured a broad pool of cassettes with a total of 35% novel gene cassettes. A majority of gene cassettes encoded resistance to aminoglycosides, heat shock protein, heavy metals, pilus secretory proteins, and twin-arginine translocases (Tat), TatA, TatB, and TatC. Both in combination and solo treatments, the diversity of gene cassettes was increased in the manure-enriched soil, however, biochar reduced the gene cassettes’ diversity and their cassettes array. Manure considerably enhanced CL1 integrons abundance and antimicrobial resistance, whereas biochar amendments significantly reduced integrons and antimicrobial resistance. The results highlighted the differential effects of biochar and manure on integrons and its gene cassette arrays, showing increased abundance of integrons and antibiotic resistance upon manure application and decrease of the same with biochar. The use of biochar alone or in combination with manure could be a beneficial alternative to mitigate the spread of antimicrobial resistance and bacterial evolution in the environment, specifically in paddy soils.